#ShamimaBegum: An analysis of social media narratives relating to female terrorist actors - Evans, C.; Da Silva, R. (Politics, 2023)
This study explores the constructions of gender in social media narratives regarding Shamima Begum, a British born woman who travelled to Syria to join Islamic State of Iraq and Syria (ISIS). Using the Twitter hashtag #ShamimaBegum – developed in response to Begum’s expressed interest in returning to the United Kingdom to give birth to her third child – we employ critical discourse analysis to examine social media users’ responses to Begum’s case across a 3-week period. We portray how the vernacular narratives constructing femininity, gender, and their relation to terrorist activity are built on the expectation that the female actor should express remorse for her actions and is judged according to certain perceptions of maternalism, religion, and victimhood. We also explore the absence of considered agency in the narratives about women engaging in and disengaging from violent activities, demonstrating the weight of race, religion, and gender in shaping narratives surrounding perceived violent women.